Gender Education Concept for Elementary Age Children - Muhammad Shaleh Assingkily; Noni Putri (Yayasan Zia Salsabila, 2022)
Gender education is an effort to instill a sense of tolerance and tolerance in children from the start. This study attempts to analyze the concept of gender education for elementary age children. The formulation of the discussion of this research includes how to internalize the values of gender in children from a very early age, educate children about the urgency of gender and events about influencing factors. This study uses an approach to the literature study method. The data source and analysis of this research study used research material data obtained from SINTA or Google Scholar. The results of this study found that (1) efforts to internalize the value of gender behavior in children can be done through a sense of equality (without anything special or not special), giving children freedom (democracy), exemplifying tolerance and equality in children (exemplary), and respecting children. other people's feelings; (2) educating children through parenting regardless of gender, fostering children's self-confidence, appreciating children's positive traits, and facilitating children's development and skills; and (3) factors that influence gender development, namely biological, social and cognitive aspects.